The Effect of Financial Anxiety, Financial Literacy, and Consumptive Lifestyle on the Welfare of Generation Z in Greater Jakarta - Michael Parlie; Samuel Tarigan (Eduvest - Journal of Universal Studies, 2025)
Generation Z in Indonesia faces mounting financial pressures, including rising living costs, housing unaffordability, and economic uncertainty, which threaten their financial well-being. This study examines the influence of financial anxiety, financial literacy, consumptive lifestyle, and parental financial support on the financial well-being of Generation Z in Greater Jakarta. Financial literacy is operationalized into knowledge, attitudes, and behaviors. Data were collected through an online survey using purposive self-selection techniques, yielding five hundred respondents aged fifteen to thirty. The instruments include financial anxiety scales, financial well-being measures, financial behaviors, and consumptive lifestyle indicators that have been adapted and tested for reliability. Exploratory factor analysis shows that financial anxiety, financial literacy behavior, consumptive lifestyle, and financial well-being each form unidimensional and reliable constructs. The results of multiple linear regression reveal that financial literacy behavior has the strongest positive effect on financial well-being, while financial anxiety has a significant negative effect. A high level of parental financial support is negatively related to financial well-being. On the other hand, knowledge of financial literacy and consumptive lifestyle do not show meaningful influence. These findings confirm that practical financial habits and money-related emotional states determine financial well-being more than theoretical financial knowledge or consumption patterns.